A composite solid polymer electrolyte incorporating MnO2 nanosheets with reinforced mechanical properties and electrochemical stability for lithium metal batteries. Issue 4 (7th January 2020) - Li, Yuhan; Sun, Zongjie; Liu, Dongyu; Gao, Yiyang; Wang, Yuankun; Bu, Huaitian; Li, Mingtao; Zhang, Yanfeng; Gao, Guoxin; Ding, Shujiang
Abstract : The mechanical properties and electrochemical stability of a PEO based composite solid polymer electrolyte are enhanced by adding MnO2 nanosheets. Abstract : A solid polymer electrolyte is expected to be useful for safe and high energy density lithium-metal batteries owing to its good flexibility and high degree of safety. The development of a polyethylene oxide (PEO) based solid electrolyte is still restrained by low ionic conductivity and unsatisfactory mechanical strength. Since MnO2 could combine with PEO chains and Li ions could undergo long-range migration on MnO2 nanosheets, MnO2 nanoflakes are chosen as fillers to improve the electrochemical and mechanical properties of a solid polymer electrolyte. A PEO/MnO2 composite solid polymer electrolyte (CSPE) displays a higher lithium ion transference number (0.378), higher ionic conductivity (1.5 times higher at 60 °C) and better tensile strength (2.3 times) than a PEO solid electrolyte. Density functional theory calculations reflect the fact that the binding energy between the PEO/Li complex and MnO2 is small and there is easy desorption of Li from PEO and migration on MnO2 nanosheets, indicating enhanced lithium ion transport in the electrolyte system. A solid-state lithium metal battery using a PEO/MnO2 CSPE delivers higher capacity (143.5 mA h g −1 after 300 cycles) than an electrolyte without fillers (61.2 mA h g −1 after 90 cycles). Soft-package lithium metal batteries with an MnO2 CSPE reveal high safety after cutting, nail and bending tests.